Play application in the educational process of students with learning difficulties: Educators’ perspectives in Greece - Kranou Kyriakides, Fotini; Med, Fani Paraschou; Kranou-Economidou, Despina (My University, 2021)
It is a well-known fact that play has an important role in a child’s life beginning in infancy and continuing to childhood. Its relationship with education is studied by numerous researchers from a wide range and the vast majority of disciplines, including educators, psychologists, speech pathologists and occupational therapists among others. Play provides the child with a magical world in which they can develop without criticism. The aim of this research article is to present the theories that have been developed around play, the process of play therapy and to present the perspectives of educators regarding the use of play in the educational process, specifically in the education of children of non-typical development.
Keywords: Education; Non-typical development; Play; Play therapy